2013
DOI: 10.3109/13645706.2012.742114
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic guided single self-linking silicone stent in pediatric external dacryocystorhinostomy

Abstract: Self-linking stents are a useful modality in pediatric patients not only to prevent stent prolapse but also to allow easy removal with minimum discomfort. Endoscopic guidance is a useful addition to this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
6
0
3
Order By: Relevance
“…Three studies did not report the complication rate. [31] Complete resolution of symptoms, negative dye disappearance test 75 Early tube loss Okumus, 2016 [32] Complete resolution of previous signs and symptoms and DDT grade 0-1 73.3 None Orhan, 1997 [33] Resolution of symptoms and previous signs 100 Epiphora with tubes in place Eshraghi, 2014 [34] Complete resolution or partial improvement 82.6 None Ali, 2013 [35] Resolution of symptoms 91 NR Engel, 2007 [10] Good clearance of fluorescein dye and/or absence of symptomatic testing 96 Conjunctival-corneal abrasion Dotan, 2015 [36] Complete resolution of all preoperative CNLDO symptoms and signs 85 Spontaneous tube loss El-Essawy, 2013 [37] Complete resolution of symptoms, no epiphora, no discharge, no increase tear lake 82.2 Cheesewiring of canaliculi, late postoperative granuloma formation Fayet, 2012 [38] Absence of symptoms after stent removal or loss 85 Keratitis, tube loss, epiphora with tubes in place Casady, 2006 [7] Complete resolution of symptoms 100 None Eloy, 2009 [39] Complete resolution of symptoms 90 Transient slight epiphora Han, 2015 [40] Disappearance of epiphora symptoms by a minimum of 2 months 89.6 Tube prolapse, tube loss Nemet, 2008 [41] Objective confirmation of free fluorescein flow to the nose 95.2 Jones tube placement Napier, 2016 [42] Complete resolution of symptoms and signs 91.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies did not report the complication rate. [31] Complete resolution of symptoms, negative dye disappearance test 75 Early tube loss Okumus, 2016 [32] Complete resolution of previous signs and symptoms and DDT grade 0-1 73.3 None Orhan, 1997 [33] Resolution of symptoms and previous signs 100 Epiphora with tubes in place Eshraghi, 2014 [34] Complete resolution or partial improvement 82.6 None Ali, 2013 [35] Resolution of symptoms 91 NR Engel, 2007 [10] Good clearance of fluorescein dye and/or absence of symptomatic testing 96 Conjunctival-corneal abrasion Dotan, 2015 [36] Complete resolution of all preoperative CNLDO symptoms and signs 85 Spontaneous tube loss El-Essawy, 2013 [37] Complete resolution of symptoms, no epiphora, no discharge, no increase tear lake 82.2 Cheesewiring of canaliculi, late postoperative granuloma formation Fayet, 2012 [38] Absence of symptoms after stent removal or loss 85 Keratitis, tube loss, epiphora with tubes in place Casady, 2006 [7] Complete resolution of symptoms 100 None Eloy, 2009 [39] Complete resolution of symptoms 90 Transient slight epiphora Han, 2015 [40] Disappearance of epiphora symptoms by a minimum of 2 months 89.6 Tube prolapse, tube loss Nemet, 2008 [41] Objective confirmation of free fluorescein flow to the nose 95.2 Jones tube placement Napier, 2016 [42] Complete resolution of symptoms and signs 91.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 However, silicone intubation is a less invasive procedure compared with external or endonasal DCR. According to our results, in older children with persistent CNLDO, silicone intubation procedure may reduce the need for DCR, which has greater morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, reopening of the NLD has only been analyzed in small case series. Previous studies have already demonstrated that this modification is feasible and does not lead to increased complications 9 , 10 , 16 . The results from our survey, which represents the first ever comparison between the two surgical methods, reveals that surgical success is similarly good in both cases, and that neither technique is clearly superior to the other.…”
Section: Discussionmentioning
confidence: 90%
“…With this approach, Bartley also made a conscious attempt to prevent scarring of the NLD after dacryolith extraction [9]. In two further case series, each comprising 11 ELD, Hui et al and Ali et al investigated the advantages of keeping the NLD open [10,16]. The Hui et al study investigated the influence of a dual loop technique passing through the NLD and the osteotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation